FORMULASI BARU EPISTEMOLOGI FIQH PEREMPUAN - M Noor Harisudin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Though the world has changed, factually, our fiqh marginalizes women and not critical of social inequality among women. The social system is no longer a patriarchal, but it’s more based on gender equality. Therefore, the existence of more moderat and friendly fiqh for women should be realized. Fiqh should be designed with epistemology based on the mashlahah of women. This article proposes a new formulation towards epistemology of women fiqh and/ or new ushul fiqh which are really friendly towards women. This article recommends that the formation of Islamic law which is tends to neglect women is a sine qua none. Reform must be arranged through the epistemological realm, methodology, and product of women fiqh. All the three go hand in hand with its main core to potitioning the women in equal place. Thus, product of women fiqh that is better suited to the changing places and times will become a true.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.735